Behaviour of damaged high-strength concrete columns strengthened with steel strapping tensioning technique - Nurhana Azlin Yahaya, 1993-, author; Abdullah Zawawi Awang, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2016